Nouvelles écritures dramatiques au Mexique : les politicités du théâtre documentaire - Lîlâ Bisiaux (IdeAs)
In Mexico, new dramatic writings use true anecdotes and testimonies as well as authentic elements of documentary theatre. This aesthetic works as a political tool: it allows denouncing or revealing a context of domination, it is offered as a response to "gore capitalism" or "necropolitics", and it criticizes modernity/coloniality by valuing at the epistemic level what the colonial imaginary had despised.